(untitled) (Research, Society and Development, 2020)
The chronic and indiscriminate use of benzodiazepines (BZD’s) can have many adverse effects, which can lead to tolerance, dependence and withdrawal crises. Thus, the objective is to identify which BZD’s are most used in Brazil, outlining the profile of users of this pharmacological class. A literature review was carried out with articles indexed in the scientific bases Scientific Electronic Library Online (Scielo), Virtual Health Library (VHL) and PubMed, in the time frame from 2010 to 2020, using the following descriptors: “Benzodiazepines”, “Use of medicines", "Disorder related to substance use", Abuse", "Intoxication". A total of 220 articles were found in the initial selection, with 97 articles from the Scielo database, 67 from the VHL and 56 from PubMed. Being listed 13 articles (Scielo: 05, VHL: 05, PubMed: 03) as relevant, which were selected for complete analysis and construction of this study. In the studies listed, the most consumed BZD’s was Lorazepam, however in cases of anxiety Clonazepam is the drug of first choice. Regarding the profile of users of BZD’s, the age group that most use these drugs is the elderly, concerning the use of high doses of BZD’s, it was observed that younger patients, male, single and less educated are more associated sensitive. We conclude then, a high prevalence of the use of BZD’s, mainly in developed countries, which can be characterized by stress, anxiety and insomnia experienced by people in their daily lives.